IMPLEMENTASI JUAL BELI LELANG PERSPEKTIF ISTISHAB - siti mahmudah (Universitas Muhammadiyah Surabaya, 2021)
This article aims to examine the sale and purchase of auctions from the perspective of istishab. Buying and selling auctions have occurred in the community and develop according to needs. However, the law regulating auction buying and selling is still a metter of debate among the public. The subject of this article is buying and selling auctions. Research method library research eith a descriptive approach. The propet Muhammad SAW to buy and sell auctions, as the practice applied by the propet Muhammad was to assist his friends in auctioning aff his slaves and the proceeds from the auctions of slaves were intended for his treatment.then the law of buying and selling auctions is permitted until there is a legal basis that can chage the law. The purpose of holding a sele and purchase auction is to assist and assist parties experiencing financial problems. Istishab, namely enforcing exixting law until a ne law is found for an event. Buying and selling auctions is allowed by islam because it does not harm others. The practice of buying and selling auctions is carried out in public and withnessed by everyone and there is not manipulation by certain partiens.Keywords: Istishab, buying and selling auction, buying and selling of auctions during the time of the Nabi MuhammadÂ